Development Of Women's Entrepreneurshıp Competence To Improve MSMEs' Performance - Setiani Setiani; Madziatul Churiyah (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This research aims to map the competency development model for women entrepreneurs to improve the performance of MSMEs. The method used is descriptive qualitative. The stages carried out started from searching for previous literature studies, collecting and filtering data, analyzing data in depth and formulating the development of women entrepreneur competency models, applying the results of developing women entrepreneur competency models in several MSMEs, compiling research reports containing descriptions, interpretations, and analysis application of the development of the competency model for women entrepreneurs. The results of developing the model for women entrepreneurs are by improving managerial skills, participating in training through online media or social media, and taking courses according to individual needs. This model can be implemented by women entrepreneurs anywhere as long as they are willing to learn and have the motivation to continue to develop. With the development of women entrepreneur competencies, their business performance will also increase.